2022
DOI: 10.1021/acscentsci.2c00151
|View full text |Cite
|
Sign up to set email alerts
|

Instant Adhesion of Amyloid-like Nanofilms with Wet Surfaces

Abstract: The adhesion and modification of wet surfaces by an interfacial adlayer remain a key challenge in chemistry and materials science. Herein, we report a transparent and biocompatible amyloid-like nanofilm that breaks through the hydration layer of a wet surface and achieves strong adhesion with a hydrogel/tissue surface within 2 s. This process is facilitated by fast amyloid-like protein aggregation at the air/water interface and the resultant exposure of hydrophobic groups. The resultant protein nanofilm adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
21
1
Order By: Relevance
“…Studies that explore the effective arrangement and polymerization of biological macromolecules at the interface have the potential to explain protein-based adhesion systems and greatly assist the design of high-performance materials, such as antibacterial adhesion, marine antifouling, , anti-biofouling, and biomedical and biomimetic systems . Due to the internal amphiphilicity and complex/sensitive three-dimensional conformation of proteins, this kind of biopolymer exhibits complicated adsorption behavior at interfaces, namely, nonspecific adsorption. , In this context, controlling protein adsorption and assembly at interfaces is always a great challenge in biology and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that explore the effective arrangement and polymerization of biological macromolecules at the interface have the potential to explain protein-based adhesion systems and greatly assist the design of high-performance materials, such as antibacterial adhesion, marine antifouling, , anti-biofouling, and biomedical and biomimetic systems . Due to the internal amphiphilicity and complex/sensitive three-dimensional conformation of proteins, this kind of biopolymer exhibits complicated adsorption behavior at interfaces, namely, nonspecific adsorption. , In this context, controlling protein adsorption and assembly at interfaces is always a great challenge in biology and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It absorbs tissue fluid around the nerve and produces shape changes, stabilizing the apposition to the nerve and providing a regenerative scaffold (Figure S14, Supporting Information). [ 58–90 ] This hydrogel platform is expected to replace microsuturing techniques, reduce surgical difficulty, and facilitate patient recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al [ 105 ] reported a transparent and biocompatible amyloid-like nanofilm that can destroy the hydration layer of a wet surface and achieves strong adhesion to a hydrogel/tissue surface within 2 s. Based on this conceptual progress, a functional therapeutic CL was fabricated by adhesion to a functionalized phase-transitioned human lactoferrin (PTHLF) nanofilm (carrying CsA) on the CL surface for DED treatment. The PTHLF nanofilms were adhered to the hydrogel CL surface by manipulating the amyloid-like aggregation.…”
Section: Hydrogel Contact Lenses For Dry Eye Treatmentmentioning
confidence: 99%
“…( G ) Release curve of the encapsulated CsA from the functionalized film. Reprinted with permission from Qin et al [ 105 ], ACS Cent. Sci.…”
Section: Figurementioning
confidence: 99%